(untitled) (Journal of Partial Differential Equations, 2012)
We considered the Cauchy problem for the fractional wave-diffusion equation D^αu-Δ|u|^m-1u+(-Δ)^β/2D^γ|u|^l-1u=h(x,t)|u|^p+f(x,t) with given initial data and where p > 1, 1 < α < 2, 0 < β < 2, 0 < γ < 1. Nonexistence results and necessary conditions for global existence are established by means of the test function method. This results extend previous works.